2007
DOI: 10.1371/journal.pmed.0040005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Funding Source and Conclusion among Nutrition-Related Scientific Articles

Abstract: BackgroundIndustrial support of biomedical research may bias scientific conclusions, as demonstrated by recent analyses of pharmaceutical studies. However, this issue has not been systematically examined in the area of nutrition research. The purpose of this study is to characterize financial sponsorship of scientific articles addressing the health effects of three commonly consumed beverages, and to determine how sponsorship affects published conclusions.Methods and FindingsMedline searches of worldwide liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(183 citation statements)
references
References 9 publications
(9 reference statements)
6
165
1
5
Order By: Relevance
“…Recipients of industrysupported grants tend to publish research and give advice that favours the sponsor (13) . A recent article by Lesser et al (18) evaluated a wide range of studies examining the health effects of three commonly consumed beverages (soft drinks, juice and milk) and concluded that industry funding may bias conclusions in favour of sponsors' products in the area of nutrition research. Although no statistically significant association between funding source and outcomes was identified in the present study, 81?3 % of industry-funded studies and 66?7 % of government-funded studies reported favourable conclusions that supported Ca supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Recipients of industrysupported grants tend to publish research and give advice that favours the sponsor (13) . A recent article by Lesser et al (18) evaluated a wide range of studies examining the health effects of three commonly consumed beverages (soft drinks, juice and milk) and concluded that industry funding may bias conclusions in favour of sponsors' products in the area of nutrition research. Although no statistically significant association between funding source and outcomes was identified in the present study, 81?3 % of industry-funded studies and 66?7 % of government-funded studies reported favourable conclusions that supported Ca supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…c) Lack of subclassification of industry-sponsored vs. independent studies. Analysis of food industry-sponsored studies demonstrates an odds ratio of a conclusion favourable to the industry of 7.61 (38). Furthermore, a meta-analysis of meta-analyses showed that 5 of 6 food industry-sponsored studies showed that sugared beverages do not cause weight gain, whereas 10 of 12 independent studies showed that they did (39).…”
Section: The Fallacies Of Systematic Reviews and Meta-analysesmentioning
confidence: 99%
“…As government funding has shrunk, concern over industry-funded research in academic settings has grown. There is a perception that it is more likely to be biased than the research supported by the government and non-profit foundations (26,27) . There is also debate around the role of academic-university partnerships in shaping research agendas, and about how these relationships should be developed and disclosed (28)(29)(30) .…”
Section: Academic Institutionsmentioning
confidence: 99%